Pioglitazone Attenuates Drug-Eluting Stent-Induced Proinflammatory State in Patients by Blocking Ubiquitination of PPAR - Zhongxia Wang; Tao Zhang; Lizhe Sun; Ruifeng Li; Yuanyuan Wei; Xiaojuan Fan; Zuyi Yuan; Junhui Liu; Tao Chen (PPAR Research)
The inflammatory response after polymer-based drug-eluting stent (DES) placement has recently emerged as a major concern. The biologic roles of peroxisome proliferator-activated receptor-γ (PPAR-γ) activators thiazolidinedione (TZD) remain controversial in cardiovascular disease. Herein, we investigated the antiinflammatory effects of pioglitazone (PIO) on circulating peripheral blood mononuclear cells (MNCs) in patients after coronary DES implantation. Methods and Results. Twenty-eight patients with coronary artery disease and who underwent DES implantations were randomly assigned to pioglitazone (30 mg/d; PIO) or placebo (control; Con) treatment in addition to optimal standard therapy. After 12 weeks of treatment, plasma concentrations of high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and matrix metalloproteinase-9 (MMP-9) were significantly decreased in PIO group compared to the Con group (P=0.035, 0.011, 0.008, and 0.012, resp.). DES-induced mRNA expressions of IL-6, TNF-α, and MMP-9 in circulating MNC were significantly blocked by PIO (P=0.031, 0.012, and 0.007, resp.). In addition, PIO markedly inhibited DES-enhanced NF-κB function and DES-blocked PPAR-γ activity. Mechanically, DES induced PPAR-γ ubiquitination and degradation in protein level, which can be totally reversed by PIO. Conclusion. PIO treatment attenuated DES-induced PPAR loss, NF-κB activation, and proinflammation, indicating that PIO may have a novel direct protective role in modulating proinflammation in DES era.